FEATURES OF USING INTERNET TECHNOLOGY - TESTING STUDENTS' KNOWLEDGE IN PSYCHOLOGICAL AND PEDAGOGICAL LITERATURE - Tokhirova L. R. (Western European Studies, 2024)
This article explores the methodology of using Internet testing to assess students' knowledge in the field of psychology and pedagogy. The work analyzes the advantages of this technology over traditional testing methods, such as saving time, increasing accessibility, the ability to automate the process, as well as providing additional tools for analyzing results. The main stages of the development and implementation of Internet tests are revealed, including drawing up questions, creating an online platform, conducting testing and analyzing the results. The author emphasizes the need to adapt technology to the specifics of the educational process in the psychological and pedagogical fields, taking into account the characteristics of the target audience and ensuring the reliability and objectivity of the data obtained. In conclusion, the importance of Internet testing as a modern tool for assessing students’ knowledge in the field of psychology and pedagogy is emphasized and directions for further research and development of this technology are outlined
Keywords: Internet testing; student knowledge; psychological and pedagogical literature